2012
DOI: 10.1088/0004-637x/752/1/7
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Spectra of Terrestrial Exoplanet Surfaces

Abstract: We investigate spectra of airless rocky exoplanets with a theoretical framework that self-consistently treats reflection and thermal emission. We find that a silicate surface on an exoplanet is spectroscopically detectable via prominent Si-O features in the thermal emission bands of 7 -13 µm and 15 -25 µm. The variation of brightness temperature due to the silicate features can be up to 20 K for an airless Earth analog, and the silicate features are wide enough to be distinguished from atmospheric features wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 71 publications
0
125
2
Order By: Relevance
“…I find similarly large albedos for a subset of the superEarths studied here. Still considering Kepler-10b, a wide range of solid surface compositions (Hu et al 2012) could match the observed excess of brightness temperature in the Kepler bandpass. Determining how mineral reflective properties evolve through molten phases with increasing temperature will be paramount to lift this degeneracy.…”
Section: Surfacesmentioning
confidence: 95%
“…I find similarly large albedos for a subset of the superEarths studied here. Still considering Kepler-10b, a wide range of solid surface compositions (Hu et al 2012) could match the observed excess of brightness temperature in the Kepler bandpass. Determining how mineral reflective properties evolve through molten phases with increasing temperature will be paramount to lift this degeneracy.…”
Section: Surfacesmentioning
confidence: 95%
“…To avoid having too many free parameters, we consider CoRoT-7b as a prototype hot SE and carry on the analysis in this study case only. Furthermore, we focus on broadband photometry, so the composition of the rock (Hu et al 2012) or the observation of molecules in a cometary tail, which requires high spectral resolution, is not examined.…”
Section: Goalmentioning
confidence: 99%
“…Naturally, observations at multiple infrared wavelengths are also desirable to observe spectral features of different molecular species and/or surface compositions (e.g., Kuiper et al 1947;Hu et al 2012). Table 1 shows that the number of planets accessible to highcontrast characterization drops steadily as the observing wavelength increases from 1.0 µm to 3.5 µm.…”
Section: Observing Wavelength: Scattered Starlight and Thermal Emissionmentioning
confidence: 99%
“…All three GSMT projects have proposed AO-assisted MIR instruments (Brandl et al 2010;Tokunaga et al 2010;Okamoto et al 2010;Hinz et al 2012). The longer wavelengths at which these instruments would operate roughly correspond to the Wien peak of cool planets' blackbody emission, thereby providing a method to measure radiometric radii (Morrison 1973), the surface compositions of airless planets (Hu et al 2012), and the potential to detect exoplanetary ozone (e.g., Rugheimer et al 2012, and references therein).…”
Section: Observing Wavelength: Scattered Starlight and Thermal Emissionmentioning
confidence: 99%